Methodological considerations for near-infrared spectroscopy assessments in rock climbers: impact of forearm morphology and optode placement - Vandenhaute, S.; Podlipný, O.; Cikotová, E.; Forrer, T.; Baláš, J. (Frontiers in Sports and Active Living, 2026)
Introduction: Near-infrared spectroscopy (NIRS) has been widely used in rock-climbing research to assess muscle oxygenation (StO2) in the flexor digitorum profundus (FDP). However, the deep anatomical location of the FDP, combined with the maximum penetration depth of ~20 mm for most NIRS devices, raises uncertainty regarding whether the currently used optode placement is adequate for studying the FDP. This study aimed to characterize forearm morphology in climbers and examine the effect of NIRS optode placement on haemodynamic outcomes.